When voter loyalty fails: party performance and corruption in Bulgaria and Romania - Chiru, Mihail; Gherghina, Sergiu (2012)
Abstract: This article identifies the determinants of party loyalty while making a distinction between government and opposition voters within an electoral cycle in the two most recent European Union members (Bulgaria and Romania). Both countries are characterized by the perception of widespread corruption and a general distrust of politicians that are likely to hinder the development of strong ties between citizens and parties. We test the explanatory potential of both traditional and revisionist theories of partisanship, suggesting that perceptions of corruption should be treated as equal to evaluations of actual performance. The statistical analysis of comparative study of electoral systems survey data emphasizes the salience of party performance evaluations for party loyalty. Corruption perceptions are significant predictors of loyalty in the Bulgarian case. Voters in both countries assess critically the performance of their preferred party whether it was part of the government or in opp